BIODIVERSITY CONSERVATION IN INDONESIAN COASTAL AREAS: ISSUES, CHALLENGES, AND MODERNISING GOVERNANCE - Izudin, Ahmad; Aditya, Rahadiyand; Khuluq, Lathiful (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
The role of stakeholders has attractively expanded, with agencies like the private and public sectors using the analysis of many challenges in biodiversity conservation. This paper explores the findings from programs of a biodiversity park called Taman Keanekaragaman Hayati (KEHATI) that have been experienced with the sharing of division work to promote a sustainable development goal, including Indramayu governments and Polytama in Indonesia. The article reflects on the changing role of stakeholders to deliver conserving biodiversity: what are problems and why these party of stakeholders should be transformed. This research aims to analyze the current conditions related to biodiversity conservation, the challenges faced, and the necessary governance changes to ensure effective conservation efforts. Field findings indicate that biodiversity conservation efforts are confronted with significant conflicts of interest. In addition, researchers discovered that development impact can be enhanced when governing rules are modernized. Complementary support is often necessary to reduce many challenges in endangered coastal area and support innovations that leads to governance transformation.